Determinants of Long-Term Contraceptive Method among Reproductive-Aged Women in Sulawesi Island (Data Analysis of IDHS 2017) - Jihan Apande; Trisari Anggondowati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Long-Term Contraceptive Methods are contraceptive methods that, once used, last for a long period, ranging from 3 years to a lifetime. LTCMs are considered highly effective compared to non-LTCMs, with a success rate above 95%. Overall, the coverage of LTCM usage in Indonesia remains low despite a noticeable increasing trend of 10.6% in 2012 and 13.2% in 2017. This coverage is far below the global average in SDGs in 2030, which was 35%, and the targets outlined in the BKKBN Strategic Plan for 2020 (25.11%) and 2024 (28.39%). Objective: The aim of this research is to identify the determinants of LTCM usage among women of reproductive age and to determine predominant the factors most associated with LTCM usage on the island of Sulawesi. Method: This cross-sectional study aims to identify the determinants of LTCM usage among reproductive-aged women in Sulawesi Island based on secondary data from the 2017 Indonesia Demographic and Health Survey (IDHS). The population in this study consists of all reproductive-aged women (15-49 years old) who are married and using contraception in the provinces of Southeast Sulawesi, South Sulawesi, West Sulawesi, Central Sulawesi, and North Sulawesi. The data utilized a survey with a complex sample design, and this taken into account during the analysis using weighting. The data analysis employed cox regression to estimate the prevalence ratio. Result: Out of 2,703 respondents, 519 (22.5%) were using LTCMs. Statistical tests indicated associations between predisposing factors such as age, education, occupation, knowledge about family planning (FP), number of children, and economic status, reinforcing factors like decision-making autonomy regarding FP, and supportive factors such as access to FP services and FP information media with LTCM usage among reproductive-aged women in Sulawesi Island. The most influential supportive factor was access to FP services in the government sector, with a 30.1% influence, having a 2.2 times higher likelihood of LTCM usage with a p-value of 0.001 and 95% CI 1.79 - 2.88. Conclusion: There is a relationship between predisposing factors such as age, education, occupation, knowledge about family planning (FP), number of children, and economic status, reinforcing factors influencing decision-making regarding family planning, and supportive factors of family planning service sources and media information on family planning, with the use of long-term contraceptive methods (LTCM) among women of reproductive age in Sulawesi Island. The most dominant factor associated is the supportive factor of family planning service sources in the government sector.